2022
DOI: 10.1097/hs9.0000000000000711
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of COVID-19 in Patients With Mantle Cell Lymphoma—Report From the European MCL Registry

Abstract: Data on outcome of patients with mantle cell lymphoma (MCL) and COVID-19 infection are limited. The European MCL (EMCL) registry is a centralized registry of the EMCL network, collecting real-world information about treatments and disease courses. During the COVID-19 pandemic, additional data on MCL patients with COVID-19 infection were collected, aiming to identify risk factors for mortality from COVID-19. In our retrospective, multicenter, international study, we collected data from 63 MCL patients with a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…45,46 Patients with MCL in particular appear to be at high risk for mortality with COVID-19. 47 Hopefully, with the ever-improving array of COVID-19 therapeutics, as well as prophylactic monoclonal antibody therapies, this will gradually become less of an issue, but we still unfortunately need to factor this into our decision making.…”
Section: Suggested Approaches To Managementmentioning
confidence: 99%
“…45,46 Patients with MCL in particular appear to be at high risk for mortality with COVID-19. 47 Hopefully, with the ever-improving array of COVID-19 therapeutics, as well as prophylactic monoclonal antibody therapies, this will gradually become less of an issue, but we still unfortunately need to factor this into our decision making.…”
Section: Suggested Approaches To Managementmentioning
confidence: 99%
“… 15 , 16 All patients in the aforementioned first-line phase 2 trials received rituximab in combination with ibrutinib, whereas the use of rituximab in this study varied between centers and was surprisingly low at 39% overall. Low usage likely reflects clinician concern during the pandemic based on reports associating rituximab with more severe COVID-19 outcomes 17 , 18 and reduced vaccine efficacy. 19 In this study, we observed a trend toward improved ORR and CR rates in patients receiving rituximab, in keeping with evidence to date; however, findings were limited by the small sample size and a bias toward the use of rituximab in more favorable prognostic groups, including those with a good performance status (ECOG status, 0-1) and low risk disease.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical outcome of COVID‐19 in patients with solid cancers and HMs has been explored in a series of studies in the early phase of the SARS‐CoV‐2 pandemic period, indicating that those with malignancies were at increased risk of severe COVID‐19 outcomes 19 . COVID‐19 disproportionately impacted lymphoma patients, with a relatively high mortality rate (13%–44%) 9,16,20,21 . The subsequent Omicron variants of SARS‐CoV‐2, which harbor multiple novel spike protein mutations, were found to have increased infectivity compared with the delta variants but decreased hospitalization rate and mortality 22 .…”
Section: Discussionmentioning
confidence: 99%